The Lambert function on the solution of a delay differential equation - Brito, Paulo (2011)
Recently, a new method for computing the analytical solution of a delay differential equation was developed considering a constant initial function. It is based on the existence of a specific class of polynomials in the delay. In this article, we extend this new method to the case of a continuous initial function. We also show the relationship between the new solution’s method and the solution expressed in terms of the Lambert function.